2015
DOI: 10.3390/ma8041442
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Behavior of Fiber-Reinforced Concrete with End-Hooked Steel Fibers

Abstract: In this paper, the compressive behavior of fiber-reinforced concrete with end-hooked steel fibers has been investigated through a uniaxial compression test in which the variables were concrete compressive strength, fiber volumetric ratio, and fiber aspect ratio (length to diameter). In order to minimize the effect of specimen size on fiber distribution, 48 cylinder specimens 150 mm in diameter and 300 mm in height were prepared and then subjected to uniaxial compression. From the test results, it was shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(92 citation statements)
references
References 9 publications
2
75
0
4
Order By: Relevance
“…(1). An empirical equation proposed by Lee et al (2015) appeared to be appropriate for predicting the compressive behavior of SFR-HSC with high-volume BFS, for both ascending and descending branches.…”
Section: Compressive Behaviorsmentioning
confidence: 99%
See 2 more Smart Citations
“…(1). An empirical equation proposed by Lee et al (2015) appeared to be appropriate for predicting the compressive behavior of SFR-HSC with high-volume BFS, for both ascending and descending branches.…”
Section: Compressive Behaviorsmentioning
confidence: 99%
“…To predict the compressive behaviors of SFR-HSC, the following equation suggested by Lee et al (2015) was adopted. …”
Section: Compressive Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…After soils reinforced with the other three kinds of plant roots were destroyed, the strength curve decreased slightly. The results showed that residual strength remained after the reinforced soils were destroyed, which improved the toughness of the soil, and related studies have also proved that fiber-reinforced materials exhibit ductile behavior after reaching their compressive strength [21]. When the soil is subjected to slight dislocation or tensile fracture, the root-soil composite system plays a certain role in reinforcing the soil.…”
Section: Unconfined Compressive Strength Testsmentioning
confidence: 86%
“…Most of failure in PC structures is caused by the failure of connection [10]. To date, there are many researches have been conducted on PC [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. However, there is limited research focused on a connection of PC using SFRC [1].…”
Section: Introductionmentioning
confidence: 99%